Partial fetotomy: technique to resolve wry neck dystocia in mare - Mubbashar Hassa; Sana Shahid; Akhtar Rasool Asif; Muhammad Ilyas Naveed; Abid Hussain Shahzad; Mumtaz Ali Khan (The Korean Society of Animal Reproduction and Biotechnology, 2020)
Foaling is a process of giving birth to foal which is prompt and forceful event in equine breeding. Dystocia is declared when 2nd stage of parturition exceeds from 20 min without fetal movements in mare. Dystocia is very challenging situation for both mare and veterinarian. Survivability of mare and foal, and subsequent fertility of mare depends on efficient management. Therefore, the current report described a rare case of wry neck (torticollis or unilateral bent neck) resulted in dystocia, that was efficiently resolved by partial fetotomy and repulsion technique in mare under field conditions. Intensive post operative care was performed to avoid infection and to achieve fertility subsequently.